A pocket style manual - Hacker, Diana, 1942- (Boston : Bedford/St. Martin's, 2004)
Presents a practical pocket reference manual that provides offers instruction on sentence structure, grammar, punctuation, and mechanics for writers and researchers.
Spiral-bound.
Includes bibliographical references (p. [228]-230) and index.
Adult
Keywords: English language -- Grammar -- Handbooks, manuals, etc; English language -- Rhetoric -- Handbooks, manuals, etc; English language -- Grammar -- Handbooks, manuals, etc; Rhetoric -- Handbooks, manuals, etc